2008
DOI: 10.1309/dgxyth0vnttqrqhd
|View full text |Cite
|
Sign up to set email alerts
|

Improving Quality of Patient Care in an Emergency Department

Abstract: The purpose of our study was to improve the quality of care in an emergency department (ED) as measured by length of stay (LOS), total turnaround time (TAT) for laboratory result reporting, and the blood culture contamination rate. Data were included for patients who had at least 1 of 5 laboratory tests performed as part of their care. The study was conducted in 2 phases. First, phlebotomy was performed by a dedicated phlebotomist or nonlaboratory personnel. The second phase added a dedicated laboratory techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…Of the five studies included in the body of evidence for phlebotomy team practice effectiveness (Table 2), all were conducted in large U.S. hospitals, two in emergency departments only (Gander [41], Sheppard [13]). One of the studies is unpublished (Geisinger Wyoming Valley, 2009, Appendix B) and four are rated “Good” study quality and one is rated “Fair.” Of the included studies, three had phlebotomy team comparison groups using only venipuncture for blood draws (Gander [41], Surdulescu [16], Weinbaum [19]) which provide more reliable evidence for estimating phlebotomy team practice effectiveness than the two studies which include both venipuncture and catheter draws in their comparison groups.…”
Section: Evidence Review Synthesis and Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the five studies included in the body of evidence for phlebotomy team practice effectiveness (Table 2), all were conducted in large U.S. hospitals, two in emergency departments only (Gander [41], Sheppard [13]). One of the studies is unpublished (Geisinger Wyoming Valley, 2009, Appendix B) and four are rated “Good” study quality and one is rated “Fair.” Of the included studies, three had phlebotomy team comparison groups using only venipuncture for blood draws (Gander [41], Surdulescu [16], Weinbaum [19]) which provide more reliable evidence for estimating phlebotomy team practice effectiveness than the two studies which include both venipuncture and catheter draws in their comparison groups.…”
Section: Evidence Review Synthesis and Resultsmentioning
confidence: 99%
“…Phlebotomy teams are applicable to a variety of hospital environments such as tertiary care, community and academic medical centers, emergency departments, adult general medical and surgical care settings [13,16,19,41]. Based on the included studies, phlebotomy team results are highly applicable across several patient groups in hospital settings, but less so in special cases where venipuncture may be less applicable such as neonatal intensive care units and critically ill patients in long term care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, differences in preanalytical procedures can explain up to 41 % of the variation of prevalence of hypercholesterolemia [8]. [10] reported that when the phlebotomy was performed in an emergency department by dedicated laboratory technologists, there was a reduction in overall turnaround time, and blood culture contamination rates dropped from 5.0 to 1.1 %.In addition, blood draws from indwelling catheters or during IV starts are more prone to hemolysis compared to venipuncture draws [11]. 3.…”
mentioning
confidence: 99%